Análisis del impacto de las Regatas Vinceñas en el turismo náutico deportivo del Cantón Vinces - Gómez Jacome, Eddy Leonel (2020)
This research has been carried out in order to know what is the contribution that leaves the nautical sport in the canton Vinces in the winter season, which was able to identify that the regattas is a massive event which attracts tourists and competitors as nationals and foreigners contributing to the economy of the canton in an excessive way which each resident is benefited. This research collects information that is recorded in the theoretical support that strengthens the bank of questions that were applied to the directors of the tourism department of the cantonal GAD, as well as to the organizers of the Vinceñas regattas. As a result of the application of investigative techniques, this is surveys and interviews, findings that describe the impact of regattas on water sports and their contribution to the tourism development of Canton Vinces. With the results obtained in the investigation carried out in this case study, it was possible to demonstrate in a closer way the object of study and reach the conclusion of the Vinceña population is prepared throughout the year to receive and own and strangers that is to say national tourists and foreigners.